2016
DOI: 10.1177/0892020616643160
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between elementary school principals’ transformational leadership and spiritual well-being

Abstract: The aim of this study was to determine the relationship between transformational leadership and spiritual well-being among elementary school principals. A correlational research or ex post facto method was used in this study. The sample population comprised 141 subjects, of which 69 were male and 72 were female. Bass and Avolio's Transformational Leadership Questionnaires and Ellison's Spiritual Well-Being Scale were used. The results obtained indicated that the assessment of domains related to transformationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
1
6
1
1
Order By: Relevance
“…[3,7] The results of the study showed western Pennsylvania nonprofit administrators' spirituality to be positively correlated with some but not all transformational leadership practices and were consistent with other similar studies found in the literature. [11,19] Mydin et al discovered more evidence of a relationship between spirituality and transformational leadership than the present study, showing spirituality to be positively correlated with most measures of transformational leadership. [4] Iyer, in contrast, found a single relationship between spirituality and connecting with others.…”
Section: Discussioncontrasting
confidence: 45%
“…[3,7] The results of the study showed western Pennsylvania nonprofit administrators' spirituality to be positively correlated with some but not all transformational leadership practices and were consistent with other similar studies found in the literature. [11,19] Mydin et al discovered more evidence of a relationship between spirituality and transformational leadership than the present study, showing spirituality to be positively correlated with most measures of transformational leadership. [4] Iyer, in contrast, found a single relationship between spirituality and connecting with others.…”
Section: Discussioncontrasting
confidence: 45%
“…The participants in this study conceptualized their use of mindfulness meditation/prayer as connected to their belief in God. They relied on their relationship with, faith in and trust in a higher being to cope with the stress and anxiety they experience as a result of their work and work intensification (Mehdinzhad and Nouri, 2016; Walker, forthcoming). For example, Principal 3 shared that when dealing with challenges such as operating with limited resources to meet work demands, he “talks to doctor God [and] also meditate…my quiet moments with meditation help me to stay present…[because] when [I] am overworked or thinking too much I feel anxious.” For this principal, meditation is a form of prayer, which he uses to stay “present.” Principal 5 described using mindfulness meditation and prayer in a similar way: “One of the things I practice…when feeling stressed…is I depend on the Lord; I try to garner my strength from him…through deep reflection.” This was a recurrent theme among the participants' responses – gathering their strength through quiet reflection on God.…”
Section: Resultsmentioning
confidence: 99%
“…For the purposes of this article, however, I focus almost exclusively on the practice as part and parcel of Christian belief, because that is how my participants conceptualized their use of the strategy. Generally speaking, spiritual belief is faith in a supernatural power; this faith can provide a sense of purpose and support when confronted with challenges (Fisher, 2001, 2011; Fisher and Ng, 2017, Mehdinzhad and Nouri, 2016; Schwebel, 2017). Researchers have argued that spiritual belief is subjective and socioculturally related to individuals' background and understanding of life, and that people can be spiritual without having any affiliation with religious groups (Bellous and Csinos, 2009; Faull, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bech, 2004;Richardson et al, 2014;Ryff, 1989) and principal wellbeing (e.g. Mahfouz and Richardson, 2021;Mehdinezhad and Nouri, 2016;OECD, 2020;Pollock and Wang, 2020;Viac and Fraser, 2020) and then generated items for each domain. We used two principles to define the content domains.…”
Section: Methodsmentioning
confidence: 99%
“…The fifth instrument is the Spiritual Well-Being Scale developed in the US by Paloutzian and Ellison (1982) to measure both religious and existential wellbeing. Mehdinezhad and Nouri (2016) used the Spiritual Well-being Scale to measure the degree of school principals' spirituality in Iran. The final instrument is the Psychological Well-Being Scale developed in the US by Ryff (1989) as a measure of positive mental health.…”
Section: Measurements Of Principal Well-beingmentioning
confidence: 99%